Early paracetamol treatment associated with lowered risk of persistent ductus arteriosus in very preterm infants. (August 2014) - Aikio, Outi; Härkin, Pia; Saarela, Timo; Hallman, Mikko
Abstract Objectives: Persistent ductus arteriosus (PDA) delays the recovery of very preterm infants (VLGA, gestation <32 weeks). Indomethacin/ibuprofen treatment and ligation of PDA have complications. As a prostaglandin synthase inhibitor paracetamol may also promote the closure of ductus arteriosus. We studied retrospectively whether early paracetamol therapy was associated with decreased incidence of PDA without adverse events. Methods: On June 2009, we introduced intravenous paracetamol during early respiratory therapy. We included 105 VLGA infants who received paracetamol before the age of 72 h. The loading dose was 20 mg/kg followed by 7.5 mg/kg every 6 hours. The 96 VLGA infants admitted from January 2008 to May 2009 without lethal congenital disease were controls. Infants dying very early were excluded, leaving 102 paracetamol-exposed and 88 controls for analysis. Results: After the introduction of paracetamol, the incidence of PDA decreased from 30.7% to 14.7% (p = 0.008). Ibuprofen treatment was given to 15 paracetamol-treated and to 26 control infants (p = 0.013). Three paracetamol-exposed and seven control infants required surgery. There was no detectable increase in adverse events. Conclusions: Annual incidence of PDA decreased after introduction of paracetamol. Efficacy and safety in promoting the early closure of ductus arteriosus remains to be established.